Mob Family Proteins: Regulatory Partners in Hippo and Hippo-Like Intracellular Signaling Pathways - Duhart, Juan Carlos; Raftery, Laurel A. (Frontiers in Cell and Developmental Biology, 2020)
Studies in yeast first delineated the function of Mob proteins in kinase pathways that regulate cell division and shape; in multicellular eukaryotes Mobs regulate tissue growth and morphogenesis. In animals, Mobs are adaptors in Hippo signaling, an intracellular signal-transduction pathway that restricts growth, impacting the development and homeostasis of animal organs. Central to Hippo signaling are the Nuclear Dbf2-Related (NDR) kinases, Warts and LATS1 and LATS2, in flies and mammals, respectively. A second Hippo-like signaling pathway has been uncovered in animals, which regulates cell and tissue morphogenesis. Central to this emergent pathway are the NDR kinases, Tricornered, STK38, and STK38L. In Hippo signaling, NDR kinase activation is controlled by three activating interactions with a conserved set of proteins. This review focuses on one co-activator family, the highly conserved, non-catalytic Mps1-binder-related (Mob) proteins. In this context, Mobs are allosteric activators of NDR kinases and adaptors that contribute to assembly of multiprotein NDR kinase activation complexes. In multicellular eukaryotes, the Mob family has expanded relative to model unicellular yeasts; accumulating evidence points to Mob functional diversification. A striking example comes from the most sequence-divergent class of Mobs, which are components of the highly conserved Striatin Interacting Phosphatase and Kinase (STRIPAK) complex, that antagonizes Hippo signaling. Mobs stand out for their potential to modulate the output from Hippo and Hippo-like kinases, through their roles both in activating NDR kinases and in antagonizing upstream Hippo or Hippo-like kinase activity. These opposing Mob functions suggest that they coordinate the relative activities of the Tricornered/STK38/STK38L and Warts/LATS kinases, and thus have potential to assemble nodes for pathway signaling output. We survey the different facets of Mob-dependent regulation of Hippo and Hippo-like signaling and highlight open questions that hinge on unresolved aspects of Mob functions.